Schwerwiegende Fehlentscheidungen im Lebensrückblick - Lengert, Andrea (Forum Komparative Kasuistik, 2009)
Both volumes deal with serious personal mistakes in the course of life. Part I, the basic research was conducted at the TU Berlin by Andrea Lengert and supervised by Prof. Dr. Gerd Jüttemann. In this exploratory qualitative project problem-centered interviews and the grounded theory approach for analyzing the data were used to examine what intra-individual processes follow a wrong decision. Part II, written by Jill Tegge, contains the results of a replication study, which was undertaken at the TU Braunschweig under the supervision of Prof. Dr. Wolfgang Schulz. The study uses comparative casuistry ("komparative Kasuistik"). In addition, an online questionnaire asking people about own errors in their past, was used to collect data.